The rocky road to rural health - I. Couper (South African Family Practice)
Rural health is featuring more prominently on the national agenda in recent times. This article offers a personal review of some aspects of rural health care in South Africa, particularly, in terms of human resources, and proposes a way forward. There have been some important advances in rural health care, such as the implementation of the district health system, the community service and Cuban doctor programmes, the rise of RuDASA and academic initiatives in rural health. Difficulties in the way of improved rural health care include the AIDS burden, the moratorium on the registration of foreign doctors, negative attitudes to non-South African doctors, loss of nursing staff and lack of a coherent approach to human resources in health care. It is proposed that a coordinated rural health strategy is needed, which may include private-public partnerships clarification of the role the doctor in primary care and a team approach to solving the problems.